Optical characterization of an amorphous organic thin film - Yakuphanoğlu, Fahrettin; Sekerci, M (Technical Univ Wroclaw, 2005)
The optical characteristics of Co(II) complex having 5,6-O-cyclohexylidene-l-amino-3-azahexane thin film were investigated by spectrometric measurements. The optical parameters, optical band gap E. and width of localized states E,, of the film were determined using the transmittance T and the reflectance R at normal incidence in the spectral range 540-660 nm. The absorption edge of the film exhibits the exponential behavior which is attributed to the electronic transition in the localized states tailed off in the indirect energy band gap of the film. The refractive index spectra of the film show normal dispersion up to about 2 eV and afterwards, the refractive index increases with increasing photon energy.
Keywords: thin film; optical constants; optical band gap